1997
DOI: 10.1038/sj.onc.1200896
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Shc docking site on Ret tyrosine kinase

Abstract: The RET proto-oncogene encodes two isoforms of a receptor type tyrosine kinase which plays a role in neural crest and kidney development. Distinct germ-line mutations of RET have been associated with the inherited cancer syndromes MEN2A, MEN2B and FMTC as well as with the congenital disorder Hirschsprung disease (HSCR), whereas somatic rearrangements (RET/PTCs) have been frequently detected in the papillary thyroid carcinoma. Despite these ®ndings, suggesting a relevant role for RET product in development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 25 publications
7
98
0
Order By: Relevance
“…We constructed a Y1062F Ret/MEN2A protein mutant (RET/MEN2A Y1062F ) and we con®rmed that, when expressed in COS-1 cells, it was correctly synthesized (Figure 7a, lower). Moreover, an immunoprecipitation with anti-Ret followed by blotting with anti-phosphotyrosine antibodies, indicated that, as reported Lorenzo et al, 1997;Arighi et al, 1997), Y1062F mutation did not alter the intrinsic kinase activity of Ret/MEN2A (see for an example Figure 7b). As expected, Y1062F mutation abrogated in vitro binding of Ret/MEN2A to the PTB domain of Shc (Figure 7a, upper).…”
Section: Oncogenic Forms Of Ret Activate Epitope-tagged Jnk1 In Cos-1supporting
confidence: 76%
See 3 more Smart Citations
“…We constructed a Y1062F Ret/MEN2A protein mutant (RET/MEN2A Y1062F ) and we con®rmed that, when expressed in COS-1 cells, it was correctly synthesized (Figure 7a, lower). Moreover, an immunoprecipitation with anti-Ret followed by blotting with anti-phosphotyrosine antibodies, indicated that, as reported Lorenzo et al, 1997;Arighi et al, 1997), Y1062F mutation did not alter the intrinsic kinase activity of Ret/MEN2A (see for an example Figure 7b). As expected, Y1062F mutation abrogated in vitro binding of Ret/MEN2A to the PTB domain of Shc (Figure 7a, upper).…”
Section: Oncogenic Forms Of Ret Activate Epitope-tagged Jnk1 In Cos-1supporting
confidence: 76%
“…Conversely, both isoforms are able to bind and to induce the tyrosine phosphorylation of Shc (Borrello et al, 1994;Lorenzo et al, 1997). In particular, Ret tyrosine residue 1062, which is common to both Ret 1072 and Ret 1114 , is part of a docking site for the Shc phosphotyrosine binding (PTB) domain Lorenzo et al, 1997;Arighi et al, 1997). Our preliminary results indicate that Y1062F mutation impairs Ret activation of endogenous Ras (Visconti et al, unpublished).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The receptor complex also includes (GPI)-anchored proteins GFRa1, 2, 3 and 4 that are required for RET dimerization and dictate ligand selectivity (Baloh et al, 2000;Scott and Ibanez, 2001). After interaction with its ligands, RET undergoes autophosphorylation and then interacts with multiple effectors such as phospholipase C, Shc, enigma, Grb2, Grb7/ Grb10, Src kinase and Ras-GAP (Santoro et al, 1994;Arighi et al, 1997;Lorenzo et al, 1997). Gainof-function mutations of the RET gene have been associated with multiple endocrine neoplasia type 2 (MEN 2), an autosomal dominant inherited cancer syndrome (Mulligan et al, 1993), whereas loss-offunction mutations of RET have been associated with Hirschsprung disease (aganglionosis, HSCR), a frequent congenital intestinal malformation (1 in 5000 live births) characterized by the absence of neural crest-derived parasympathetic neurons of the hindgut (Edery et al, 1994;Romeo et al, 1994).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%